Innovation and circular economy in tourism enterprises in northern Manabí (Ecuador) - Garcia Reinoso, Nelson (2026)
This study aimed to analyze the adoption of innovation and circular economy practices among tourism enterprises in northern Manabí, Ecuador, from a sustainability-oriented perspective to identify existing dynamics, limitations, and opportunities within the territory. The research followed an exploratory–descriptive approach, based on primary data collected through structured surveys administered on a 1-7 Likert scale, to 196 tourism enterprises registered in the official tourism registry. Data were processed using descriptive statistics in IBM SPSS Statistics v25.0. The results revealed significant gaps in the implementation of circular economy practices: 63.8% of respondents reported no knowledge of its principles, 75% did not apply circular waste management practices, and only 5.6% reported sustainabilityoriented innovations. In contrast, relatively higher implementation levels were observed in practices related to decent work (36.2%) and energy efficiency (34.7%). Based on these findings, five strategic guidelines were proposed to strengthen the transition toward more sustainable tourism entrepreneurship models in the region. The main implication of the study was that advancing sustainability in these territories requires not only entrepreneurial willingness but also capacity building, institutional articulation, and technical support.